2021
DOI: 10.1021/acscentsci.1c00599
|View full text |Cite
|
Sign up to set email alerts
|

Twisting of 2D Kagomé Sheets in Layered Intermetallics

Abstract: Chemical bonding in 2D layered materials and van der Waals solids is central to understanding and harnessing their unique electronic, magnetic, optical, thermal, and superconducting properties. Here, we report the discovery of spontaneous, bidirectional, bilayer twisting (twist angle ∼4.5°) in the metallic kagomé MgCo 6 Ge 6 at T = 100(2) K via X-ray diffraction measurements, enabled by the preparation of single crystals by the Laser Bridgman… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…These are related to each other by a sixfold screw axis along c , and an inversion center is located between the Kagome nets, making the full structure centrosymmetric, even though a single distorted Kagome net breaks inversion symmetry (Figure d). The distorted Kagome net at low temperature is distinct from AV 3 Sb 5 family, , a similar distortion has been seen in the Kagome metals MgCo 6 Ge 6 , LaRu 3 Si 2 , and YRu 3 Si 2 , and some of the phases are superconductors but show no sign of magnetic or CDW transitions above T c . It is worth noting that although a magnetic transition at low temperature (18 K) was detected in the previous magnetic susceptibility study, no magnetic transition signal was observed between 50 and 300 K . This may be related to the distortion of the Co Kagome nets, which is inverted between the two layers and may influence magnetization; future experiments such a muon spin relaxation may help to explicitly understand the magnetism and its relation to the resistive transition in Yb 0.5 Co 3 Ge 3 .…”
Section: Resultsmentioning
confidence: 57%
“…These are related to each other by a sixfold screw axis along c , and an inversion center is located between the Kagome nets, making the full structure centrosymmetric, even though a single distorted Kagome net breaks inversion symmetry (Figure d). The distorted Kagome net at low temperature is distinct from AV 3 Sb 5 family, , a similar distortion has been seen in the Kagome metals MgCo 6 Ge 6 , LaRu 3 Si 2 , and YRu 3 Si 2 , and some of the phases are superconductors but show no sign of magnetic or CDW transitions above T c . It is worth noting that although a magnetic transition at low temperature (18 K) was detected in the previous magnetic susceptibility study, no magnetic transition signal was observed between 50 and 300 K . This may be related to the distortion of the Co Kagome nets, which is inverted between the two layers and may influence magnetization; future experiments such a muon spin relaxation may help to explicitly understand the magnetism and its relation to the resistive transition in Yb 0.5 Co 3 Ge 3 .…”
Section: Resultsmentioning
confidence: 57%
“…27 Thus, we conclude that the specimens measured here are small-bandgap semiconductors. These bandgaps are much smaller than those observed in most kagoméminerals, but also far from the metallicity observed in materials such as Fe 3 Sn 2 , MgCo 6 Ge 6 , 28 and KV 3 Sb 5 , 8−10,29 and place Ni 3 (HIB) 2 and Cu 3 (HIB) 2 much farther from the insulating limit than most QSL candidates. It is also interesting to compare our Ni 3 (HIB) 2 and Cu 3 (HIB) 2 results to those of other recently discovered kagoméMOFs.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…Works reporting using a floating zone furnace for PbTiO 3 had very fast growth speeds (100 mm/h) and were largely unsuccessful due to the evaporation of PbO leading to an unstable, collapsing zone . Recent progress in the use of laser diode floating zone (LDFZ) furnaces in synthesizing a wide variety of materials, including those with high vapor pressures, encourages revisitation of this technique as applied to PbTiO 3 . Here we report the growth of bulk crystals (4 cm length, ∼5 mm OD) of PbTiO 3 using the LDFZ.…”
Section: Introductionmentioning
confidence: 99%